2003
DOI: 10.1046/j.1468-2982.2003.00514.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Daily Headaches: Clinical Profile in Indian Patients

Abstract: Chronic daily headache (CDH) remains a relatively unexplored entity in India. Misconceptions are common, unnecessary investigations often done and inappropriate therapy prescribed. Analgesic overuse is seldom recognized. The present report appears to be the first of its kind from India. CDH has been defined as headaches occurring more than 15 days per month for more than 3 months (secondary causes excluded). Over 2 years (1998-1999) 849 cases (49.6% of all primary headaches) were seen. More than 1 year's follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
54
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(65 citation statements)
references
References 18 publications
9
54
0
2
Order By: Relevance
“…Consistent with other studies, this study reflects the fact that headaches are more common in women. [11][12][13] In the present study, out of 100 patients with Chronic headache, primary headache was the predominant type accounting for 82% as compared to Secondary headache seen only in 18%.Consistent with our finding, AP Jain et al showed primary headache as the predominant type with a prevalence of 92.5% and remaining 7.5% with secondary headache.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with other studies, this study reflects the fact that headaches are more common in women. [11][12][13] In the present study, out of 100 patients with Chronic headache, primary headache was the predominant type accounting for 82% as compared to Secondary headache seen only in 18%.Consistent with our finding, AP Jain et al showed primary headache as the predominant type with a prevalence of 92.5% and remaining 7.5% with secondary headache.…”
Section: Discussionsupporting
confidence: 91%
“…In a recent study from India [11], 849 patients with chronic daily headaches were reported, and 16% had CTTH, 1.5% had new daily persistent headache and 82% were reported to have transformed/chronic migraine. In the latter group, a large proportion had drug overuse and probably also coexisting tension-type headache, although only one headache diagnosis was applied to each individ- Table 1 Common subtypes of chronic daily headache in relation to the diagnostic criteria of the International Headache Society (IHS), second edition [7].…”
Section: General Populationmentioning
confidence: 99%
“…The last year prevalence is approximately 10%-12% for migraine, 35%-68% for episodic tension-type headache and 4%-5% for chronic daily headache, including 2%-3% with chronic tensiontype headache (CTTH) and 1.5%-3% with medication overuse headache (MOH), when the 1988 IHS criteria and the CDH definition by Silberstein et al [2] are applied [8][9][10][11][12]. However, in clinical studies from specialised headache clinics, the picture is completely different.…”
Section: Epidemiologymentioning
confidence: 99%
“…In another older series of 630 CDH patients from Houston Migraine Clinic, 78% of patients had the socalled transformed migraine, with mixed features of migraine and TTH [17]. Furthermore, 73% of all patients used excessive amounts of symptomatic medication on a daily basis [12], and thus a clear diagnostic picture of the underlying primary headaches from such clinical series is difficult to delineate.…”
mentioning
confidence: 99%
“…Unfortunately, most clinical and some epidemiologic publications do not report the coexisting TTH, only the migraines or the common denominator CDH [9,10,17].…”
mentioning
confidence: 99%